The Spirit in Matthew: Righteousness and Obedience - Charette, Blaine (Pneuma, 2021)
Abstract It is clear that the Spirit of God plays a very important role in Matthew’s account. It is also important to note that Matthew refers to the Spirit in ways that are distinctive. For example, among the evangelists only Matthew speaks of the Spirit of God, and Matthew is unique in the NT in referring to the Spirit of the Father. This manner of nuancing the Spirit is analogous to the varied ways in which Matthew describes the kingdom, a concept qualified by such terms as “heaven,” “God,” “Father,” and “Son of Man.” This similarity is appropriate since a further unique feature of the Gospel is that Matthew alone decisively associates the Spirit of God with the presence of the kingdom of God. This discussion will focus first on Jesus’s experience of the Spirit and then on the work of the Spirit in the redemptive or kingdom activity of Jesus.